2017
DOI: 10.1177/2051415817706045
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the efficacy and tolerability of mirabegron, a β3-adrenoceptor agonist, for the treatment of overactive bladder: Systematic review and network meta-analysis

Abstract: Overactive bladder (OAB) is a common condition affecting approximately 11% of individuals worldwide. One of the newest treatment options for OAB symptoms is mirabegron. The objective of this network meta-analysis is to evaluate the extent of the efficacy and tolerability of mirabegron compared both to placebo and first-line anticholinergic pharmacotherapies. Methods: Articles were identified through the MEDLINE, EMBASE, and Cochrane databases using the search term 'mirabegron'. All original, prospective, rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…CrI credible interval, DAR darifenacin, FES festerodine, MIR mirabegron, OR odds ratio, OXY oxybutynin, PL placebo, SA sensitivity analysis, SOL solifenacin, TOL tolterodine, TRO trospium chloride because of a low event count across trials, highlighting that this event may occur with lower frequency than is commonly believed. Overall, these findings are in line with previously published NMAs, where mirabegron was found to be significantly more efficacious than placebo and similarly efficacious to antimuscarinics, but with a statistically and clinically favorable safety profile [47][48][49][50]. It should also be noted that previous NMAs of patients with OAB from all age groups have generally indicated a significant improvement on efficacy outcomes associated with solifenacin relative to mirabegron.…”
Section: Discussionsupporting
confidence: 89%
“…CrI credible interval, DAR darifenacin, FES festerodine, MIR mirabegron, OR odds ratio, OXY oxybutynin, PL placebo, SA sensitivity analysis, SOL solifenacin, TOL tolterodine, TRO trospium chloride because of a low event count across trials, highlighting that this event may occur with lower frequency than is commonly believed. Overall, these findings are in line with previously published NMAs, where mirabegron was found to be significantly more efficacious than placebo and similarly efficacious to antimuscarinics, but with a statistically and clinically favorable safety profile [47][48][49][50]. It should also be noted that previous NMAs of patients with OAB from all age groups have generally indicated a significant improvement on efficacy outcomes associated with solifenacin relative to mirabegron.…”
Section: Discussionsupporting
confidence: 89%
“…Common side effects of mirabegron include hypertension, headache, and urinary tract infection. 40,44 A systematic review and network meta-analysis of 13 randomized, controlled trials identified significantly higher incidences of tachycardia and nasopharyngitis with mirabegron 50 mg versus placebo and of cardiac arrhythmia with mirabegron 100 mg versus placebo, and a significantly lower rate of cardiac arrhythmia versus tolterodine ER 4 mg. 49 Mirabegron prescribing information states that mirabegron may increase blood pressure and recommends periodic blood pressure measurements, but notes that in clinical trials of monotherapy or combination therapy with solifenacin 5 mg, mean increases in systolic and diastolic blood pressure from placebo were~0.5-1 mmHg with mirabegron 50 mg. 40 Although compliance data are limited, in a retrospective UK database study of patients who received a prescription for an OAB medication, the median time to discontinuation for mirabegron was 169 days, while that for each of the antimuscarinic agents analyzed was substantially shorter (range, 30-78 days to discontinuation). 50 Two additional b3 agonists, vibegron and solabegron, are under investigation in phase 3 and phase 2 clinical trials, respectively.…”
Section: Second-line Therapy: Pharmacologic Treatment Antimuscarinic Agentsmentioning
confidence: 99%